2018
DOI: 10.1159/000495219
|View full text |Cite
|
Sign up to set email alerts
|

A Perfused Microfluidic System to Study the Differentiation of Neural Stem Cells in vitro

Abstract: Introduction: Due to the ability to mimic in vivo cellular microenvironments, the development of multicell culture systems has received increasing interest for use as research models and serving as platforms for drug evaluation. Methods: In this study, we developed a perfused microfluidic system to resemble the in vivo intercellular environment and applied it to study the differentiation from neural stem cells into neurons. Results: As determined by immunofluorescence chemistry and quantitative real-time PCR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This is similar to the results reported in a previous study where the cells were differentiated into astrocytes using a medium supplemented with N-2 supplement [ 51 ]. FBS is also widely used for the differentiation of NSPCs into neurons [ 45 , 46 , 52 ]. Similar to previous studies, the cells grown in a medium with FBS showed high expression of β3-tubulin; however, the expression of MBP and GFAP was low.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the results reported in a previous study where the cells were differentiated into astrocytes using a medium supplemented with N-2 supplement [ 51 ]. FBS is also widely used for the differentiation of NSPCs into neurons [ 45 , 46 , 52 ]. Similar to previous studies, the cells grown in a medium with FBS showed high expression of β3-tubulin; however, the expression of MBP and GFAP was low.…”
Section: Discussionmentioning
confidence: 99%